2018
DOI: 10.1111/jth.14263
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐adjusted tinzaparin for the prevention of venous thromboembolism after bariatric surgery

Abstract: Background Patients undergoing bariatric surgery are at moderate to high risk of venous thromboembolism (VTE). The optimal dose and duration of anticoagulant prophylaxis is uncertain. Objective To evaluate the safety of extended-duration weight-adjusted tinzaparin after bariatric surgery. Patients/methods We conducted a single-center retrospective cohort study of consecutive patients undergoing bariatric surgery who received weight-adjusted tinzaparin 4500-14 000 IU daily (75 IU kg rounded to the nearest prefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…26 A single, large study on tinzaparin retrospectively included 1,212 bariatric patients with a median BMI of 47.9kg/m 2 . 27 Low bleeding and VTE rates were observed with weight-based dosing of 75 IU/kg, and anti-Xa measurements showed no signs of accumulation. Notably, the utilized dose was higher than the recommended according to the product information (50 IU/kg).…”
Section: Prophylaxis In Bariatric Surgerymentioning
confidence: 95%
“…26 A single, large study on tinzaparin retrospectively included 1,212 bariatric patients with a median BMI of 47.9kg/m 2 . 27 Low bleeding and VTE rates were observed with weight-based dosing of 75 IU/kg, and anti-Xa measurements showed no signs of accumulation. Notably, the utilized dose was higher than the recommended according to the product information (50 IU/kg).…”
Section: Prophylaxis In Bariatric Surgerymentioning
confidence: 95%
“…In one prospective study, the rate of postoperative VTE and bleeding was 0% for 735 patients who underwent bariatric surgery and received extended duration (1-3 wk) thromboprophylaxis with LMWH [16]. Similarly, Tseng et al [6], in a retrospective study of 817 patients, reported a 0.5% rate of postoperative VTE in those managed with extended duration (10 days) of tinzaparin.…”
Section: Discussionmentioning
confidence: 94%
“…Obesity is an independent risk factor for VTE; a body mass index (BMI) ≥30 kg/m 2 has been shown to increase the VTE risk 2-fold [5]. The reported postoperative incidence of VTE after bariatric surgery, however, varies widely, from 0.2 to 5% [1,6]. Similarly, the rate of bleeding after surgery varies from 0% to 6% [7].…”
Section: Introductionmentioning
confidence: 99%
“…VTE: Individuals with obesity are at an increased risk of VTE, though the overall rate following metabolic surgery has been reported to be < 1%[ 127 - 129 ]. A preoperative risk assessment model to stratify candidate by VTE risk was devised by Fink et al [ 130 ] using the following variables: procedure type, patient history of VTE, male sex, BMI, age, and operative time > 3 h. By this scheme, 97% were classified into low-risk groups with a predicted VTE risk of < 1%.…”
Section: Preoperative Evaluation and Optimization Of Pulmonary Functionmentioning
confidence: 99%